IMPACT COVID-19 TERHADAP RENTABILITAS BANK PERKREDITAN RAKYAT KONVENSIONAL DI KABUPATEN SUKOHARJO - POERNANINGRUM SEKAR WARDHANI; ISMUNAWAN ISMUNAWAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to determine the effect of the Covid-19 pandemic as measured using the ratio of NPL (Non Performing Loan), BOPO, LDR (Loan Deposit Ratio), and NIM (Net Interest Margin) as independent variables on rentability measured using the ROA (Return) ratio. on Assets) as the dependent variable on conventional rural banks in Sukoharjo district. The study population was 16 BPR registered with the Financial Services Authority. From this population, 12 samples were taken that met the criteria of the purposive sampling technique. The object of research is the BPR quarterly financial reports for 2019-2020, which consist of 4 quarters in 2019 and 3 quarters in 2020. Data collection techniques use indirect observation, which is to collect financial report data through the official website www.ojk.go.id. Quantitative methods with secondary data are the methods used in research. Data analysis used multiple linear regression with SPSS 19 application. This study resulted that the NPL, LDR, and NIM variables partially did not have a significant effect on ROA, while BOPO partially had a significant effect on ROA. However, if simultaneously the four independent variables have a significant effect on ROA.